Strathmore : Our 20-Minute Neighbourhood : 20-Minute Neighbourhood Pilot Program. - Victoria. Department of Environment, Land, Water and Planning ([Melbourne] : Environment, Land, Water and Planning, 2019)
"...all about 'living locally' - giving people the ability to meet most of their everyday needs within a 20-minute walk from home, with access to safe cycling and local public transport options..."--Page 2.
Cover title.
Includes bibliographical references.
Also available online. Address as at 22/11/19
Keywords: Neighbourhood Pilot Program (Vic.); City planning -- Victoria -- Strathmore; Neighborhood planning -- Victoria -- Strathmore; Community development -- Victoria -- Strathmore -- Planning; Australian